Dentine matrix protein 1 (DMP-1) is a marker of bone-forming tumours. - Kashima, T; Dongre, A; Oppermann, U; Athanasou, N (2013)
Dentin matrix protein 1 (DMP-1) is highly expressed by osteocytes and is a non-collagenous matrix protein found in dentin and bone. In this study, we determined the expression of DMP-1 in mature and immature human bone and examined whether DMP-1 is useful in distinguishing osteoid/bone-forming tumours from other primary and secondary bone tumours. DMP-1 expression was immunohistochemically determined in paraffin sections of a wide range of benign and malignant primary bone tumours and tumour-like lesions (n = 353). DMP-1 mRNA expression was also examined in osteosarcoma and fibrosarcoma cell lines as well as bone tumour specimens (n = 5) using real-time PCR. In lamellar and woven bone, DMP-1 was expressed in the matrix around osteocyte lacunae and canaliculi; osteoblasts and other cell types in the bone were negative. Matrix staining of the osteoid and bone was seen in bone-forming tumours including osteoma, osteoid osteoma, osteoblastoma and osteosarcoma. DMP-1 staining was also seen in fibrous dysplasia, osteofibrous dysplasia and chondroblastoma and in reactive bone in solitary bone cysts and aneurysmal bone cysts. DMP-1 was not expressed in the tumour component of other bone neoplasms including Ewing sarcoma, chondrosarcoma, leiomyosarcoma, fibrosarcoma, giant cell tumour of bone and metastatic carcinoma. DMP-1 mRNA was expressed in osteosarcoma cell lines and tumour samples. DMP-1 is a matrix marker expressed around osteocytes in human woven and lamellar bone and is useful in identifying osteosarcoma and other bone-forming tumours.